Performances of Four Real-Time PCR Assays for Diagnosis of Pneumocystis jirovecii Pneumonia - Sasso, Milène (J Clin Microbiol, 2016)
Pneumonia due to Pneumocystis jirovecii (PCP) is a frequent infection among HIV-positive or other immunocompromised patients. In the past several years, PCR on pulmonary samples has become an essential element for the laboratory diagnosis of PCP. Nevertheless, very few comparative studies of available PCR assays have been published. In this work, we evaluated the concordance between four real-time PCR assays, including three commercial kits, AmpliSens, MycAssay, and Bio-Evolution PCR, and an in-house PCR (J. Fillaux et al. 2008, J Microbiol Methods 75:258–261, doi:http://dx.doi.org/10.1016/j.mimet.2008.06.009), on 148 pulmonary samples. The results showed concordance rates ranging from 81.6% to 96.6% (kappa, 0.64 to 0.93). Concordance was excellent between three assays: the in-house assay, AmpliSens, and the MycAssay PCR (kappa, >0.8). The performances of these PCR assays were also evaluated according to the classification of the probability of PCP (proven, probable, possible, or no final diagnosis of PCP) based on clinical and radiological signs as well as on the direct examination of bronchoalveolar lavage samples. In the proven PCP category, Pneumocystis jirovecii DNA was detected with all four assays. In the probable PCP category, the in-house PCR, AmpliSens, and the MycAssay PCR were positive for all samples, while the Bio-Evolution PCR failed to detect Pneumocystis jirovecii DNA in two samples. In the possible PCP category, the percentage of positive samples according to PCR varied from 54.5% to 86.4%. Detection of colonized patients is discussed. Finally, among the four evaluated PCR assays, one was not suitable for colonization detection but showed good performance in the proven and probable PCP groups. For the three other assays, performances were excellent and allowed detection of a very low fungal burden.